The readiness of communal wool farmers to comply with sustainability standards in the Eastern Cape province, South Africa - Jordaan, Daniel du Plessis Scheepers (University of Pretoria, 2023)
Mini Dissertation (MSc (Agricultural Economics))--University of Pretoria, 2023.